The silver squad : rebels with wrinkles - Essen, Marty (Victor, MT : Encante Press, 2025)
"Barry and Beth, high school sweethearts separated by time and circumstance, find themselves reunited at the Blue Lagoon Village senior living center in Minneapolis. Now both seventy, they rekindle their relationship only to discover how differently time has shaped them. Beth has blossomed into a free spirit with a goth flair, while Barry has transformed into the curmudgeon he swore in his youth he'd never become. Determined to prove you're never too old to make a difference, they set off on a daring road trip across America as Silver Squad vigilantes. Along the way, they pick up a woman on the run from her abusive husband, confront a mass shooter with only a can of SPAM for defense, and become accidental celebrities along the way."--
Keywords: Love in old age -- Fiction; Man-woman relationships -- Fiction; Vigilantism -- Fiction; Older people -- Travel -- Fiction; Automobile travel -- United States -- Fiction; Humorous fiction